Apgar Scores at 10 Minutes and Outcomes in Term and Late Preterm Neonates with Hypoxic-Ischemic Encephalopathy in the Cooling Era - Ayrapetyan, Marina; Talekar, Kiran; Schwabenbauer, Kathleen; Carola, David; Solarin, Kolawole; McElwee, Dorothy; Adeniyi-Jones, Susan; Greenspan, Jay; Aghai, Zubair H. (American Journal of Perinatology, 2019)
Objective To determine the short-term outcomes (abnormal brain magnetic resonance imaging [MRI]/death) in infants born with a 10-minute Apgar score of 0 who received therapeutic hypothermia and compare them with infants with higher scores.Study Design This is a retrospective review of 293 neonates (gestational age ≥ 35 weeks) born between November 2006 and October 2015 admitted with hypoxic-ischemic encephalopathy who received therapeutic hypothermia. Results of brain MRIs were assessed by the basal ganglia/watershed scoring system. Short-term outcomes were compared between infants with Apgar scores of 0, 1 to 4, and ≥5 at 10 minutes.Results Eight of 17 infants (47%) with an Apgar of 0 at 10 minutes survived, having 4 (24%) without abnormalities on the brain MRI and 7 (41%) without severe abnormalities. There was no significant difference in the combined outcomes of “death/abnormal MRI” and “death/severe abnormalities on the MRI” between infants with Apgar scores of 0 and 1 to 4. Follow-up data were available for six of eight surviving infants, and none had moderate or severe neurodevelopmental impairment.Conclusion In the cooling era, 47% of infants with no audible heart rate at 10 minutes and who were admitted to the neonatal intensive care unit survived; 24% without abnormalities on the brain MRI and 41% without severe abnormalities.
Keywords: Apgar 0; neonatal encephalopathy; hypothermia; outcomes